Frequency and coinfection between genotypes of human papillomavirus in a population of asymptomatic women in northern Peru - Ponce-Benavente, Luis (2018)
Objective: Describe the prevalence of HPV genotypes via PCR and DNA sequencing in 397 women who attended to the gynecological outpatient center in the Hospital Regional Docente de Cajamarca from March to September 2017. Results: A positive PCR result for HPV was observed in 121 cervical samples. A high-risk genotype was found in 63.6% (77/121) of patients, a probably oncogenic type in 23.1% (28/121) and a low-risk type in 7.4%. Among the high-risk genotypes, HPV-31 was the most common one present in 20% (21/77), followed by HPV-16 in 11.4% (12/77). Coinfections between two or more genotypes were observed in 12 cases.